(untitled) (Annals of the University of Bucharest. Philosophy Series, 2025)
Humanity is transforming from a pure biological organism to a biodigitally converged being. The transformation has been hastened by rapid increases in power and commercialization of advanced technologies such as brain-computer interfaces and artificial intelligence. All indicators point towards a trend of continual acceleration away from baseline biology as the human becomes the source of computing rather than simply a user. While mainstream transhumanists laud such development as exemplative of progress towards a grand vision of man and machine becoming one, a variety of concerns, both philosophical and technological, are readily observable. This paper focuses on one such concern associated with the intersection of brain-computer interfaces and embedded artificial intelligence on those devices. Within this intersection, the biodigital convergence of a brain-computer interface is known to produce issues related to user agency. However, what is not known is how brain-computer interfaces with embedded AI may dampen or amplify such issues and what potential technological solutions may exist to ameliorate the agency problems. Furthermore, there is a lack of an applied epistemology to guide any such understanding. To that end, this paper describes a propositional metadata schema which may serve as a brain-computer interface action labeling mechanism for the information output by the biodigital system. The theoretical and practical significance of the schema are explained and ideas for future work are provided.